Immunocytochemistry A Practical Guide for Biomedical Research - Burry, Richard W. (Springer New York : Imprint: Springer, 2010)
Immunocytochemistry is a microscopic method that uses antibodies to localize proteins in tissue sections and cell cultures. Dr. Burry’s book is the first practical guide to planning, performing, and evaluating immunocytochemical experiments designed for novice immunocytochemists. This book’s predominant orientation is academic, focusing only on the most productive methods, with a primary emphasis on animal-based research tissues. The clear descriptions of the methods are easily followed and the specific design charts show how to plan an experiment. Included are a series of experimental cases exploring actual mistakes that demonstrate the approaches presented. Immunocytochemistry is no longer considered a specialized technique - Immunocytochemistry: A Practical Guide for Biomedical Research showcases this mainstream morphological approach in an accessible and exciting manner.